The mechanism of recrystallization of binary aluminum and tin bronzes - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2024)
A nanostructural mechanism for recrystallization of binary aluminum and tin bronzes has been developed. First, structure-forming nanocrystals of α-phases, β-phases and γ-phases are formed from elementary nanocrystals of copper, aluminum, tin and their free atoms. The crystallization centers of microcrystals of phases are formed from them. From these centers, structure-forming nanocrystals of phases, free atoms of copper, aluminum, tin, microcrystals of α-phases, β-phases and γ-phases of binary aluminum and tin bronzes are formed.